PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS IX PADA MATERI PERKEMBANGBIAKAN HEWAN DI SMPN 5 SURABAYA - Fatmah, Fatmah (Indonesian Journal of Science Learning (IJSL), 2023)
The low science learning outcomes are usually caused by learning that is still teacher-centered (monotonous), in the learning process the teacher still uses the lecture method and the few learning resources used by students. This study aims to describe the learning outcomes of class IX students of SMP Negeri 5 Surabaya in the subject of Animal Breeding through the Problem Based Learning model. This type of research used pre-experiment, the research method used was a quantitative descriptive approach, the research subjects were 30 students of class IX-A, the data collection technique used pre-test and post-test. The pre-test and post-test were used to find out the learning outcomes of class IX-A students on Animal Breeding material, the results obtained from the pre-test were, as many as 17 students or 56.66% of 100% of students had understood the animal breeding material . While the lowest score was 4 students out of 30 children or 13.33%, they were still in the very low category in understanding animal breeding material. With this the average pre-test score for class IX-A is 83.22, the post-test results obtained are as many as 22 students out of 30 children or 73.33% having the highest score. While the lowest is 3 children or the equivalent of 10% of the total. While the average student score in the post test has an average of 84.66. Thus, the application of the problem based learning model is very effective as evidenced by the high mean scores of the post-test and pre-test conducted.